On some species of Omaliini McLeay, 1825 of Chile (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2022)
New taxonomic and faunisic data for five species of Omaliini McLeay, 1825 of Chile are provided. Two species are (re-) described: Omaliopsis russata (Fairmaire & Germain, 1861) and O. struyvei sp.n. (southern Chile). The genus Stenomalium Blackwelder, 1943, previously known from Australian and Oceanic regions, is recorded from South America for the first time: S. picipenne (Fauvel, 1867) comb. nov. (from Omalium Gravenhorst, 1802) and unnamed S. sp. A new faunistic material for Xenanthobium andicola (Fauvel, 1867) is given. The habitus of all species, and aedeagi and abdominal segments of three species (except Stenomalium) are provided.